146k views
2 votes
If f(x) = 2x – 1 and g(x) = x^2 – 2, find [g ◦ f](x).

User Ryan Lyu
by
6.0k points

2 Answers

3 votes


(g\circ f)(x)=(2x-1)^2-2=4x^2-4x+1-2=4x^2-4x-1

User SANDEEP MACHIRAJU
by
6.0k points
3 votes

Answer:


4x^2 -4x -1

Explanation:

Given functions,


f(x) = 2x - 1-----(1)


g(x) = x^2 -2-----(2)

∵ (gof)(x) = g[f(x)] ( Composition of functions )


\implies (gof)(x) = g(2x-1) ( From equation (1) )


=(2x-1)^2 - 2 ( From equation (2) )


=4x^2 + 1 - 4x - 2


=4x^2 -4x -1

User Darkjh
by
6.1k points